A scientificity and feasibility evaluation of COVID-19 clinical studies registered in China - Tao, Liyuan (Ann Transl Med, 2020)
BACKGROUND: An outbreak of novel coronavirus infection in Wuhan, China, in early 2020 has now developed into a worldwide pandemic. Researchers in China and around the world have conducted many clinical studies on the scientific response to infectious diseases. Here, we review and summarize the registration protocols for clinical research of the novel coronavirus disease (COVID-19). METHODS: We searched all the registered studies in all platforms under the International Clinical Trials Registry Platform (ICTRP) of the World Health Organization (WHO) before March 11, 2020, screened the registration scheme for novel coronavirus, extracted the basic research information, research quality, feasibility information, and described the scientificity and feasibility of interventional research. RESULTS: From January 23, 2020 to March 11, 2020, 379 clinical studies were registered, 260 were therapeutic studies among them, and 96.8% studies were conducted in China by Chinese researchers. Some studies were registered 2 weeks just after the virus was identified, and up to 22 studies registered for one day. The number of interventional studies was greater than observational studies (263 vs. 116). Among the interventional studies, nearly 50% studies were funded, 87.7% were randomized, and 79.4% of the primary outcome indicators were objective. However, the sample size of the studies ranged from 60 to 200, with the total sample size accounting for 40% of the confirmed infected population. More than 60% studies might face the problem of insufficient sample size. CONCLUSIONS: COVID-19 clinical study registration has been considerable, rapid, and high quality in study design. However, the feasibility of these studies may still be problematic, especially in such as insufficient sample size, poor coordination among multidisciplinary teams, and weak quality control in the research process.